The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1186/cc8007
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculatory changes and skeletal muscle oxygenation measured at rest by non-infrared spectroscopy in patients with and without diabetes undergoing haemodialysis

Abstract: IntroductionHaemodialysis has direct and indirect effects on skin and muscle microcirculatory regulation that are severe enough to worsen tolerance to physical exercise and muscle asthenia in patients undergoing dialysis, thus compromising patients' quality of life and increasing the risk of mortality. In diabetes these circumstances are further complicated, leading to an approximately sixfold increase in the incidence of critical limb ischaemia and amputation. Our aim in this study was to investigate in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 42 publications
(52 reference statements)
2
31
0
Order By: Relevance
“…This may have been the case due to the lack of suitable techniques for clinical microvascular monitoring. Studies using skin and muscle oxygenation have recently shown impaired microvascular response in patients undergoing dialysis [10,11]. However, these techniques focus only on the peripheral microvasculature.…”
Section: Introductionmentioning
confidence: 99%
“…This may have been the case due to the lack of suitable techniques for clinical microvascular monitoring. Studies using skin and muscle oxygenation have recently shown impaired microvascular response in patients undergoing dialysis [10,11]. However, these techniques focus only on the peripheral microvasculature.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Previous NIRS studies in the hemodialysis unit have found a lower baseline cerebral tissue oxygenation in hemodialysis patients compared to healthy controls 23 and peritoneal dialysis patients, 24 and a greater hemoglobin concentration and reduced microvascular compliance measured in the calf muscle as a result of hemodialysis. 25 The effect of hemodialysis on the regional cerebral blood flow has been investigated with Xenon ventilation scintigraphy, where a mild reduction in cerebral blood flow was shown following as compared to before hemodialysis, 26 and with magnetic resonance imaging, where dialysis patients had lower cerebral blood flow than healthy controls. 23 The effect on large artery blood flow velocity has been assessed with transcranial Doppler ultrasound, revealing a significant decrease in blood flow velocity following dialysis as compared to prior to hemodialysis.…”
Section: Introductionmentioning
confidence: 99%
“…In response to ischemia, it also allows evaluation of dynamic changes in microcirculation. Using NIRS, the changes in skeletal muscle oxygenation have been demonstrated in chronic heart failure patients at rest and during exercise [20,29], in patients undergoing haemodialysis [21], during abdominal aortic and cardiac surgery [30,31], and in patients with peripheral arterial disease [32], cirrhosis [33], septic shock [22,23], and metabolic myopathies [34]. NIRS has been already applied to demonstrate the effect of IPC on changes in myocardial oxygenation in dogs; IPC has been induced by repeated periods of coronary occlusion [35].…”
Section: Discussionmentioning
confidence: 99%
“…Near infrared spectroscopy (NIRS) has been used to assess peripheral microvascular function in a variety of clinical settings [19][20][21][22][23]. Illuminating an infrared band of 680-800 nm NIRS exploits the difference in absorption spectra between the oxygenated and deoxygenated hemoglobin and partly myoglobin and thus assesses the balance between local arterial supply and cellular oxygen consumption within the muscle tissue.…”
Section: Introductionmentioning
confidence: 99%